2015
DOI: 10.1371/journal.pone.0127806
|View full text |Cite
|
Sign up to set email alerts
|

Assortative Mating and the Reversal of Gender Inequality in Education in Europe: An Agent-Based Model

Abstract: While men have always received more education than women in the past, this gender imbalance in education has turned around in large parts of the world. In many countries, women now excel men in terms of participation and success in higher education. This implies that, for the first time in history, there are more highly educated women than men reaching the reproductive ages and looking for a partner. We develop an agent-based computational model that explicates the mechanisms that may have linked the reversal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(99 citation statements)
references
References 51 publications
(92 reference statements)
5
88
0
6
Order By: Relevance
“…As we can see in Table 2, in the majority of countries, couples in which the woman is more educated than the man are more common than couples in which the man is more educated than his partner. This result is in line with recent trends in educational assortative mating that have been found across European and non-European countries (Esteve et al 2012;Grow and Van Bavel 2015).…”
Section: The Main Explanatory Variable: Educational Pairingssupporting
confidence: 90%
See 1 more Smart Citation
“…As we can see in Table 2, in the majority of countries, couples in which the woman is more educated than the man are more common than couples in which the man is more educated than his partner. This result is in line with recent trends in educational assortative mating that have been found across European and non-European countries (Esteve et al 2012;Grow and Van Bavel 2015).…”
Section: The Main Explanatory Variable: Educational Pairingssupporting
confidence: 90%
“…While educational homogamy remains the most common mating pattern in Europe (Blossfeld and Timm 2003;Hamplova 2009;De Hauw et al 2017), marked changes in heterogamous couples have occurred. Recent studies have shown that unions in which the man is more educated than the woman (hypergamy) are now less common than unions in which the woman is more educated than the man (hypogamy) (Esteve et al 2012;Grow and Van Bavel 2015;De Hauw et al 2017).…”
Section: Non-marital Family Formation and The Role Of Educational Assmentioning
confidence: 99%
“…Indeed, the expansion of higher education among women and resulting patterns of assortative mating affect family formation, fertility, and divorce (Schwartz and Han 2014;Grow and Van Bavel 2015). Contrary to expectations, highly educated women are not more likely to remain single.…”
Section: Women's New Role and Its Implications For Family Dynamicsmentioning
confidence: 99%
“…Alternatively, it has been suggested that an increase in gender symmetry in education and earning capacity would raise the desirability of highly educated women as marriage partners, since their contribution to the household income may be expected to be greater than in the past (Blossfeld and Müller 2002). Indeed, recent studies from Europe and other developed countries have suggested that there has been a decline in traditional marriage unions in which the man is better educated than the woman, and an increase in married couples in which the woman is better educated than the man (Esteve et al 2012;Grow and Van Bavel 2015).…”
Section: Education and Family Formation Patterns In Britainmentioning
confidence: 99%